The importance of quality assurance in molecular genetic laboratories - Mannhalter, C. (Hämostaseologie, 2010)
Several challenges arise from the wide application of molecular genetic analyses, among them the need to introduce rules to evaluate molecular genetic test systems as well as test laboratories. This article specifically addresses laboratories performing molecular genetic tests for diagnosis, prevention and therapy of various diseases. The topics that will be discussed will support these laboratories to achieve and sustain a high quality and avoid mistakes and errors. The article covers important preanalytic, analytic and postanalytic aspects in regard to molecular genetic testing as well as quality management issues. In addition laboratory responsibilities, training of personnel, data protection issues, as well as informed consent aspects will be discussed. Beyond that, some molecular genetic methods will be dealt with in regard to potential quality criteria.
Keywords: Quality management; molecular genetic testing